Keadaan Pendidikan Indonesia Pada Masa Penjajahan Jepang (Jurnal Motivasi Pendidikan dan Bahasa, 2024)
This article discusses Education in Indonesia during the Japanese Occupation. The purpose of this paper is to describe the influence of the Japanese occupation on education in Indonesia. This paper is the result of a historical study using heuristics, criticism, interpretation and historiography steps. During the Indonesian occupation, Japan carried out several educational policies, namely cultivating Japanese culture, reforming the education system, policies on curriculum and policies to Islamic education. So that during the colonial period, Japan had implemented policies in the field of education which had implications for various types and levels of education in Indonesia.